2010
DOI: 10.1016/j.eurpsy.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver psychoeducation for first-episode psychosis

Abstract: This study confirms that caregiver psychoeducation specifically for first-episode psychosis directly improves knowledge of the illness overall and, in particular, knowledge of medication. Gender is not a factor in this, while the lack of any socioeconomic differences dispels the myth that patients in lower socioeconomic groups are disadvantaged because their caregivers know less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…The effect sizes ranged from small ( g = −0.1, P < .05) to very large ( g = −1.32, P < .005). All effect sizes for care burden were significant, except for the 12‐month’ follow up in Chien's () mutual support group ( g = −0.42, P > .05). On the whole, the effect sizes of the 4 outcomes had an upward trend of improvement over the longer term, suggesting that the intervention effects were maintained or potentially improved over time.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The effect sizes ranged from small ( g = −0.1, P < .05) to very large ( g = −1.32, P < .005). All effect sizes for care burden were significant, except for the 12‐month’ follow up in Chien's () mutual support group ( g = −0.42, P > .05). On the whole, the effect sizes of the 4 outcomes had an upward trend of improvement over the longer term, suggesting that the intervention effects were maintained or potentially improved over time.…”
Section: Resultsmentioning
confidence: 89%
“…Each study was checked to ascertain if all outcomes mentioned in the study methods/aims were fully reported in the papers, and any trial protocols that were registered/published online were also cross‐checked. Five studies (Calvo, 2014; Chien, ; Chien, Chan, & Thompson, ; Chien, Norman, & Thompson, ; Chien & Wong, ) were graded as unclear risks because they did not register their protocols, and therefore, the absence of selective reporting could not be confirmed. In addition, 1 study (Leavey et al, ) reported all outcomes but only extracted a few subscale scores of the instruments to describe the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Given that psychosocial factors, as outlined by family dynamics (high levels of CC and FB), are related to the course of psychosis from the early stages of the illness in addition to putative biological mechanisms, our findings suggest that early intervention with the families of patients with psychosis, may reduce patients' relapse. Extensive literature has demonstrated the positive impact of psychoeducational interventions in improving family environment, reducing relapse and easing the burden of care [70][71][72][73][74][75][76]. Thus, parameters associated with EE and FB should be examined by the therapeutic team in everyday practice, and if we suspect dysfunctional dynamics, interventions should be made.…”
Section: Discussionmentioning
confidence: 97%
“…These studies evaluated the usefulness of a multifamily group psychoeducation in improving family members' knowledge and understanding about psychosis and related management strategies. The result showed improvement in the family members' knowledge (Cabral & Chaves, 2010), understanding, and management of psychosis from pretest to posttest (McWilliams et al, 2010;Mullen et al, 2002). An exception to the above trend, the pretest and posttest study of Gonzalez-Blanch et al (2010) evaluated the effect of eight sessions of multifamily group psychoeducation on carers' burden and EE.…”
Section: Outcomes Of Non-randomized and Uncontrolled Studiesmentioning
confidence: 99%